Disability and other human questions - Goodley, Dan, 1972- (SocietyNow., 2020)
Dan Goodley draws on two decades of research and writing and weaves personal stories, scholarly literature, social media and other cultural narratives together with concepts from the interdisciplinary field of disability studies. His argument is simple: disability invites great insight into the wider project of understanding the human condition. Goodley argues that the study of disability is of great importance in its own right but also has much to offer us all in considering what it means to be human in the 21st Century. Chapters address questions such as 'who's allowed to be human?'; 'are human beings dependent?'; and 'what does it mean to be human in the digital age?' and respond to these questions in ways that get us thinking about how we might productively engage with, listen to and understand one another.